Potential Drug Interactions and Drug Risk during Pregnancy and Breastfeeding: An Observational Study in a Women's Health Intensive Care Unit - Amanda Canato Ferracini; Aline Teotonio Rodrigues; Marília Berlofa Visacri; Rebeca Stahlschmidt; Nice Maria Oliveira da Silva; Fernanda Garanhani Surita; Priscila Gava Mazzola (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Introduction In the pregnancy-puerperal cycle, women may develop complications that require admission to the Intensive Care Unit (ICU). Thus, special attention to pharmacotherapy is necessary, particularly to potential drug interactions (PDIs) and to the effect of the drugs on the fetus and newborn. Objective The aim of this study was to determine the profile of PDIs and the potential risk of drugs used during pregnancy and breastfeeding among patients admitted to the ICU. Methods We conducted an observational, cross-sectional and prospective study, including pregnant and breastfeeding women admitted to the ICU at the Women's Hospital of a university in the city of Campinas, Brazil, for one year. Online databases were used to identify and classify the PDIs and the potential risk of the drugs used during pregnancy and breastfeeding. Results We evaluated 305 prescriptions of 58 women, 31 pregnant and 27 breastfeeding, and 284 (91%) prescriptions presented PDIs. A total of 175 different combinations of PDIs were identified in the prescriptions, and adverse effects caused by the simultaneous use of drugs were not actually observed in the clinical practice. A total of 26 (1.4%) PDIs were classified as contraindicated. We identified 15 (13.8%) drugs prescribed with risk D, and 2 (1.8%) with risk X for pregnant women, as well as 4 (4.9%) drugs prescribed with high risk for breastfeeding women. Conclusions This study demonstrates that there is a high incidence of PDIs in prescriptions. Most drugs used by pregnant and breastfeeding women at the ICU did not present serious risks to their fetus and newborns, but sometimes drugs with risk D or X are necessary in the course of the treatment.